Implementation of Waste Processing from the Source by the Traditional Village of Cagaan, Tampaksiring District, Gianyar Bali - Made Yaya Sawitri; Dewa Ketut Suryawan; Anak Agung Sagung Putri Risa Andriani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2020)
The Caga Traditional Village, which is located in Pejeng Kangin Village, Tampak Siring District, is one of the traditional villages that is currently seriously developing the village's potential as a tourist village. One of the efforts to improve that is now being promoted is regarding the cleanliness of the village. However, currently there is no comprehensive system capable of managing most of the waste generated by villagers. This village already has a waste bank but it only manages around 30% of the total waste generated. Organic waste which is much larger in quantity is still dumped in the